Strengthening Political Party Ideology as an Effort to Improve the Quality of Democracy in Indonesia: Penguatan Ideologi Partai Politik dalam Upaya Peningkatan Kualitas Demokrasi Indonesia - Eduard Awang Maha Putra; Lalu Aria Nata Kusuma; Fahrurrozi Iman Jayadi Syahid; Novia Salfat Anggraini (Universitas Islam Indonesia, 2024)
The shift in the role of ideology in political parties, which was initially a guideline or direction for political parties, has begun to shift and be sidelined by an excessive orientation towards power, patrons, or certain political figures and popularity. Currently, many members of political parties are present without a sufficiently deep understanding of the ideology and main ideas of their party, so this study aims to reconstruct the strengthening of political party ideology to improve the quality of Indonesian democracy. The formulation of the problem discussed in this study is the shift in the role of ideology in political parties in Indonesia; and how the ideal reconstruction of the strengthening of political party ideology. The research method used is normative legal research, using a legislative approach and a conceptual approach. The results of the study show that the relationship between ideology and political parties, namely ideology is a set of ideas that influence the goals and programs of political parties. The history of the development of political party ideology in Indonesia began in the early post-independence period which emphasized stream politics in policy making. However, most political parties today do not pay attention to the quality of their members but only prioritize popularity, wealth, and strong personalities to attract public votes. Strengthening the ideology of political parties that will have an impact on improving the quality of democracy in Indonesia can be done in several ways, namely by limiting the term of office of the general chairman of political parties, optimizing political education for party cadres, and providing additional requirements that stipulate that party cadres who can be nominated by political parties in the General Election are cadres who have been members of the party for a certain time.Key Words: Ideology, Political Parties, Democracy AbstrakPergeseran peran ideologi pada partai politik yang awalnya merupakan pedoman atau arah bagi partai politik pada faktanya mulai bergeser dan dikesampingkan oleh orientasi berlebihan terhadap kekuasaan, patron atau tokoh politik tertentu dan popularitas. Saat ini banyak anggota partai politik hadir tanpa adanya pemahaman yang cukup mendalam terkait ideologi dan pokok-pokok pikiran partainya, sehingga penelitian ini bertujuan untuk merekonstruksi penguatan ideologi partai politik dalam upaya peningkatan kualitas demokrasi Indonesia. Adapun rumusan masalah yang dibahas pada penelitian ini yaitu bagaimana pergeseran peran ideologi pada partai politik di Indonesia; dan bagaimana rekonstruksi ideal terhadap penguatan ideologi partai politik. Metode penelitian yang digunakan adalah penelitian hukum normatif, dengan menggunakan pendekatan perundang-undangan dan pendekatan konseptual. Hasil penelitian menunjukan bahwa hubungan antara ideologi dan partai politik yakni ideologi merupakan seperangkat gagasan yang memengaruhi tujuan dan program partai politik. Sejarah perkembangan ideologi partai politik di Indonesia dimulai sejak awal pasca kemerdekaan yang lebih menonjolkan politik aliran dalam pengambilan kebijakan. Namun kebanyakan partai politik dewasa ini tidak memperhatikan kualitas daripada anggotanya melainkan hanya mementingkan popularitas, harta kekayaan, dan ketokohan yang kental untuk menggaet suara masyarakat. Penguatan ideologi partai politik yang akan berdampak pada peningkatan kualitas demokrasi di Indonesia dapat dilakukan dengan beberapa cara yakni melalui limitasi masa jabatan ketua umum partai politik, mengoptimalkan pendidikan politik untuk kader partai, dan memberikan persyaratan tambahan yang mengatur bahwa kader partai yang dapat diusung oleh partai politik dalam Pemilu adalah kader yang telah menjadi anggota partai pada jangka waktu tertentu.Kata Kunci: Ideologi, Partai Politik, Demokrasi